Dendritic cell targeted HIV‐1 gag protein vaccine provides help to a recombinant Newcastle disease virus vectored vaccine including mobilization of protective CD8+ T cells. Issue 1 (4th December 2017) - Ngu, Loveline N.; Nji, Nadesh N.; Ambada, Georgia; Ngoh, Apeh A.; Njambe Priso, Ghislain D.; Tchadji, Jules C.; Lissom, Abel; Magagoum, Suzanne H.; Sake, Carol N.; Tchouangueu, Thibau F.; Chukwuma, George O.; Okoli, Arinze S.; et al.
Abstract: Introduction: Recombinant Newcastle Disease virus (rNDV) vectored vaccines are safe mucosal applicable vaccines with intrinsic immune‐modulatory properties for the induction of efficient immunity. Like all viral vectored vaccines repeated inoculation via mucosal routes invariably results to immunity against viral vaccine vectors. To obviate immunity against viral vaccine vectors and improve the ability of rNDV vectored vaccines in inducing T cell immunity in murine air way we have directed dendritic cell targeted HIV‐1 gag protein (DEC‐Gag) vaccine; for the induction of helper CD4 + T cells to a Recombinant Newcastle disease virus expressing codon optimized HIV‐1 Gag P55 (rNDV‐L‐Gag) vaccine. Methods: We do so through successive administration of anti‐DEC205‐gagP24 protein plus polyICLC (DEC‐Gag) vaccine and rNDV‐L‐Gag. First strong gag specific helper CD4 + T cells are induced in mice by selected targeting of anti‐DEC205‐gagP24 protein vaccine to dendritic cells (DC) in situ together with polyICLC as adjuvant. This targeting helped T cell immunity develop to a subsequent rNDV‐L‐Gag vaccine and improved both systemic and mucosal gag specific immunity. Results: This sequential DEC‐Gag vaccine prime followed by an rNDV‐L‐gag boost results to improved viral vectored immunization in murine airway, including mobilization of protective CD8 + T cells to a pathogenic virus infection site. Conclusion: Thus, complementary prime boost vaccination, in which prime and boost favor distinct types of T cell immunity, improves viral vectored immunization, including mobilization of protective CD8 + T cells to a pathogenic virus infection site such as the murine airway. Abstract : In complementary prime boost vaccination we have exploited helper CD4 T cells induced by a dendritic cell targeted HIV‐1 gag protein vaccine to provide help to a recombinant NDV‐gag vaccine. This improved protective T cell immunity in murine airway.